Th-MYCN Mice with Caspase-8 Deficiency Develop Advanced Neuroblastoma with Bone Marrow Metastasis - Teitz, Tal (2013)
Neuroblastoma, the most common extracranial pediatric solid tumor, is responsible for 15% of all childhood cancer deaths. Patients frequently present at diagnosis with metastatic disease, particularly to the bone marrow (BM). Advances in therapy and understanding of the metastatic process have been limited due in part, to the lack of animal models harboring BM disease. The widely employed transgenic model, the Th-MYCN mouse, exhibits limited metastasis to this site. Here we establish the first genetic immunocompetent mouse model for metastatic neuroblastoma with enhanced secondary tumors in the BM. This model recapitulates two frequent alterations in metastatic neuroblasoma, over-expression of MYCN and loss of caspase-8 expression. Mouse caspase-8 gene was deleted in neural crest lineage cells by crossing a Th-Cre transgenic mouse with a caspase-8 conditional knockout mouse. This mouse was then crossed with the neuroblastoma prone Th-MYCN mouse. While over-expression of MYCN by itself rarely caused bone marrow metastasis, combining MYCN overexpression and caspase-8 deletion significantly enhanced BM metastasis (37% incidence). Microarray expression studies of the primary tumors mRNAs and microRNAs revealed extracellular matrix (ECM) structural changes, increased expression of genes involved in epithelial to mesenchymal transition, inflammation and down-regulation of miR-7a and miR-29b. These molecular changes have been shown to be associated with tumor progression and activation of the cytokine transforming growth factor beta (TGF-β) pathway in various tumor models. Cytokine TGF-β can preferentially promote single cell motility and blood borne metastasis and therefore activation of this pathway may explain the enhanced BM metastasis observed in this animal model.